Adapting teaching styles to accommodate learning preferences for effective hospital development. - Eshleman KY (Progress in Transplantation, 2008)
Hospital development professionals in organ procurement organizations engage inmany roles in the hospital. The important role of educator requires making the mostof each teaching opportunity by understanding the characteristics of the learningaudience and applying proven principles of adult educational design, with a focuson collaborative learning and variety in presentation techniques. The goal is toprovide effective education, enabling hospital staff to transfer this learning to thejob setting, with the outcome of facilitating a supportive process that saves livesthrough organ donation.